2020
DOI: 10.17794/rgn.2020.3.2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Geological Properties of Dimension Stones on the Prediction of Specific Energy (Se) During Diamond Wire Cutting Operations

Abstract: Given the increasing demand for dimension stones, mining operations in quarries have always been an important branch of mining engineering. Among different techniques, diamond wire cutting is one of the most common methods of dimension stone mining. A reliable assessment and accurate prediction of diamond wire cutting performance are essential for feasibility analysis and operational planning in this area. This performance depends on factors such as physical, mechanical, and textural properties of the rock and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The conventional method of quarrying in these quarries is the diamond wire-cutting method, which has been used since 1985 and is still used in 90% of dimension stone quarries today (Özçelik et al, 2002;Servet et al, 2014). The advantages of this method include high cutting speed, more production efficiency, and increased block production (Khoshouei et al, 2020). Figure 7 shows a quarry bench being quarried by diamond wire-cutting machines.…”
Section: Case Studymentioning
confidence: 99%
“…The conventional method of quarrying in these quarries is the diamond wire-cutting method, which has been used since 1985 and is still used in 90% of dimension stone quarries today (Özçelik et al, 2002;Servet et al, 2014). The advantages of this method include high cutting speed, more production efficiency, and increased block production (Khoshouei et al, 2020). Figure 7 shows a quarry bench being quarried by diamond wire-cutting machines.…”
Section: Case Studymentioning
confidence: 99%
“…Khoshouei et al 2020 measured sawing energy on a laboratory diamond wire saw. Tests were carried out on samples of diorite, syenite, gabbro, granite and andesite (Figure 3), [13]. The results showed that the density, abrasiveness and p-wave velocity have the highest correlation with specific energy.…”
Section: The Influence Of Rock Properties On the Sawing Efficiency Of...mentioning
confidence: 99%
“…In the subject of rock mechanics and other technical properties, the concept of anisotropy is well-known. A theoretical investigation of the elastic anisotropy of a rock mass with regular joints was the first step in understand- ing how joints affect this property (Morland 1976;Khoshouei et al, 2020). The significance of rock mass anisotropy is emphasized and the connection between rock anisotropy and stress, deformability, and strength of a rock mass having a regular single joint set is discussed .…”
Section: Introductionmentioning
confidence: 99%